An Analysis of Students’ Speaking Ability at SMA Pembangunan Padang - Ifani Ramadhani; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2023)
This study aimed to describe the students’ speaking ability and then investigate the causes of their problems in speaking. The population of this research was the 12th grade of natural science consists of 92 students. The sample was taken through proportional random sampling and the number of the sample was 30 students. The instrument of this research was speaking test in the form of role play and interview. The result of the analysis showed that the students’ speaking ability was in the poor category and they faced some problems related to grammar, fluency, vocabulary, and pronunciation. Then, their problems in speaking were caused by teaching materials, teaching techniques, and teaching media. For teaching materials, 70% of respondents said that grammar, vocabulary, and pronunciations were a source of problems, they did not understand grammar because grammar had many rules, they did not have enough vocabulary because they did not get new vocabulary when learning and for pronunciations, they did not know how to pronounce words correctly. Then for the teaching technique, 73% of respondents said that this was due to a lack of speaking practice in class and also due to an inappropriate teaching style where the teacher only focused on completing the material so there was not much communication in class. Then for the teaching media, 63% of respondents said that the teacher did not provide an example of how to pronounce a word. The findings suggest pedagogical implications for promoting the students to speak English such as the teachers joining the training or workshop to improve their teaching materials, teaching method, and teaching media. Then, teach the component of speaking; grammar, fluency, vocabulary, and pronunciation specifically with appropriate techniques, and give more opportunities for the students to express themselves by giving various spoken English activities. Finally, the school should develop a more effective English-speaking environment by making an English club.